Profiling of gene and exosomal microRNA as therapy targets and biomarkers of cisplatin resistance in triple negative breast cancer stem cell-like subpopulation - Koh, May Zie (2021)
Breast cancer is the leading cause of death in women worldwide. Among different breast cancer subtypes, triple negative breast cancer (TNBC) which is defined by lack of oestrogen receptor, progesterone receptor and human epidermal growth factor receptors 2 possesses more aggressive behaviour than other breast cancer subtypes. Besides, TNBC is strongly associated with recurrence of metastatic breast cancer. One of the effective drugs used for TNBC treatment is cisplatin that inhibits DNA replication and dissociates p63 and p73, the transcription factors that are co-expressed exclusively in TNBC, thus leading to apoptosis of TNBC. However, the efficacy of cisplatin is compromised over time, resulted in cisplatin resistance and eventually cancer relapse. Cancer stem cells (CSCs) was proposed to contribute to the development of cisplatin resistance in breast cancer.